The Analysis Of The Influence Of Product Design And Packaging On Customers’ Interest In Buying - Farida Umi Choiriyah; Khittah Ashilah; Istiadah (International Journal of Entrepreneurship and Tourism, 2023)
Micro, small and middle class enterprises (MSME) are one of the most important sectors for the economic progress of developing countries, for example Indonesia. The problem in this research is the method of making tape which still uses limited tools, design and packaging forms which tend not to be varied. From the research results,it is known that there is a significant effect of product design (X1) on customers’ buying interest (Y), that when there is an improvement in product design, consumer buying interest will increase. However, there is no significant effect of packaging (X2) on purchasing interest (Y), it means that if there is no improvement in packaging, there will be no reduction in consumers’ purchasing interest. It can also be concluded that product design and packaging have a simultaneous effect on customers’ buying interest. This means that every time there is an improvement in product design and packaging form, consumer buying interest will increase.